Derivatization procedures and their analytical performances for HPLC determination in bioanalysis. (24th November 2020) - David, Victor; Moldoveanu, Serban C.; Galaon, Toma
Abstract: Derivatization, or chemical structure modification, is often used in bioanalysis performed by liquid chromatography technique in order to enhance detectability or to improve the chromatographic performance for the target analytes. The derivatization process is discussed according to the analytical procedure used to achieve the reaction between the reagent and the target compounds (containing hydroxyl, thiol, amino, carbonyl and carboxyl as the main functional groups involved in derivatization). Important procedures for derivatization used in bioanalysis are in situ or based on extraction processes (liquid–liquid, solid‐phase and related techniques) applied to the biomatrix. In the review, chiral, isotope‐labeling, hydrophobicity‐tailored and post‐column derivatizations are also included, based on representative publications in the literature during the last two decades. Examples of derivatization reagents and brief reaction conditions are included, together with some bioanalytical applications and performances (chromatographic conditions, detection limit, stability and sample biomatrix).